Aminoglycoside Resistance and Possible Mechanisms in Campylobacter Spp. Isolated From Chicken and Swine in Jiangsu, China - Zhang, Xiaoyan; Zhou, Qian; Tang, Mengjun; Pu, Junhua; Zhang, Jing; Lu, Junxian; Zhang, Yunzeng; Gao, Yushi (Frontiers in Microbiology, 2021)
Campylobacter is a major foodborne pathogen in humans, and previous studies reported a high prevalence of gentamicin-resistant Campylobacter isolates from food-producing animals in China. This study aimed to investigate the aminoglycoside resistance of Campylobacter isolated from chicken and swine in Jiangsu province, China and understand the possible mechanisms responsible for aminoglycoside resistance. One hundred and eighty-five Campylobacter isolates of chicken and swine origins in 2017 and 2018 were analysed for gentamicin and kanamycin resistance. Some aminoglycoside resistance genes were selected for PCR detection in all strains. The genomic DNAs of two strains with high resistance to gentamicin were used as donors to subject NCTC11168 to natural transformation. The transformants were investigated by whole-genome sequencing and analyzed comparatively with NCTC11168. In total, 30.5% (29/95) of C. jejuni isolates and 42.2% (38/90) of C. coli isolates were resistant to gentamicin and kanamycin. The prevalence of the aph(2")-If gene and aac(6')-Ie/aph(2")-Ia gene was 65.4% (121/185) and 36.2% (67/185) in Campylobacter isolates, respectively. The aadE-sat4-aphA-3 cluster was identified in 8.7% and 20.4% of all Campylobacter isolates in each year. With each donor DNA, aminoglycoside resistant transformants were obtained. The transformants showed ≥128-fold increases in the MICs of gentamicin, kanamycin and tobramycin. A 5200-bp segment was found to be inserted between the highly conserved genes Cj0299 and panB of Campylobacter. A total of 9.7% (18/185) strains showing high resistance to aminoglycosides had this segment by PCR detection. The genetic diversity of the insertion-fragment positive strains was determined by MLST, and seven sequence types were identified for these strains.